Acne vulgaris and rosacea as a cosmetic and psychological problem - Sroka, Grażyna (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2024)
This study presents the results of a survey conducted among 47 students (18 girls and 29 boys aged 13–14) of primary schools from the Podkarpackie Voivodeship (Southern Poland). The aim of the study was to self-assess the knowledge of young people about the types of acne and ways of dealing with this problem. The survey results showed that for both girls and boys this is an embarrassing problem and therefore they try to cover up the skin lesions using methods known to them. Most respondents feel embarrassed when talking about skin problems. In relation to their own complexion problems, a significant number of respondents do not believe that they can please others and are afraid of other people judging their appearance. Girls are more sensitive to this type of problems. Most respondents are aware that acne can also affect adults, but do not know any further details about it.